Effects of treatments and fermentation time on phenolic compounds, glycoalkaloid contents, and antioxidant capacity of industrial potato waste - Afaka, Muhammad Surajo; Suyub, Iswan Budy; Nobilly, Frisco; Yaakub, Halimatun (Universiti Putra Malaysia, 2024)
Potato processing plants generate waste in the form of peels, pulp, and rejects, which is estimated to be around 12–20 % of their total production volume. Potato peels, pulp, and unmarketable potatoes can be processed and incorporated into animal feed formulations. However, there is a limited information on phenolic compounds from industrial potato waste (IPW) subjected to short-term solid-state fermentation. Bioactive compounds could be improved via solid-state fermentation. Lactiplantibacillus plantarum (MW296876), Saccharomyces cerevisiae (MW296931), and Aspergillus oryzae (MW297015) were purposely selected to ferment IPW at 0, 24, 48, and 72 hr in a two-factor factorial design (treatment × fermentation time). The fermented products were analysed for phytochemical compounds such as total phenolic content (TPC), total flavonoid content (TFC), glycoalkaloid (GLA) content, and antioxidant capacity. The results revealed that the bioactive compounds, except phytic acid, had a significant interaction between treatment and fermentation time. Alpha solanine significantly (p<0.05) decreased while α chaconine increased (p<0.05) with fermentation time across all the treatments except in the control and L. plantarum treatment groups. IPW inoculated with L. plantarum significantly influenced the solubility of GLA compared to other treatment groups. Antioxidant capacity increased (p<0.05) across the fermentation time; at 48 hr of fermentation, L. plantarum had the highest (p<0.05) antioxidant capacity than S. cerevisiae and A. oryzae. Among the three inocula, L. plantarum (MW296876) consistently increased TPC, antioxidant activity, and solubility of both GLA and tannin.